Flow pattern and heat transfer in a tightly-spaced finned channel - Chua, Leok Poh. (2008)
Experiments and numerical simulations have been carried out to investigate the buoyancy-induced flow patterns and heat transfer characteristics of airflow through a horizontal rectangular channel in which the floor and the two sidewalls are heated and the ceiling is cooled. The study is conducted at the Reynolds numbers ranging from 20 to 100 and Rayleigh numbers ranging from 100 to 4200. This work is motivated by heat transfer problems in microelectronic systems, and the channel, with an aspect ratio (A=b/d, where b and d are width and height of the channel) equals to 6, is used to simulate a finned heat sink in a densely-packed-electronic enclosure with low Reynolds and Rayleigh numbers.